A Systematic Review of the European Rapid Alert System for Food and Feed: Tendencies in Illegal Food Supplements for Weight Loss - Koncz, Dorottya; Tóth, Barbara; Roza, Orsolya; Csupor, Dezső (Frontiers in Pharmacology, 2021)
Background: Slimming products represent a dynamically growing group of food supplements worldwide. The efficacy of safely usable natural ingredients is usually below consumers’ expectations. Certain manufacturers add unauthorized or prohibited ingredients to weight loss supplements in order to increase their efficacy. Hence, many of these products are adulterated and may pose a risk to the consumers’ health. Aims: The aim of our work was to give an overview on natural ingredients used in slimming products, to summarize the frequently used synthetic adulterants and also to assess the trends of adulterated and illegal food supplements in the European Union based on the warnings of the Rapid Alert System for Food and Feed (RASFF) in the time period of 1988–2019. Methods: Reports between 1988-2019 were extracted from the RASFF portal on January 1, 2020. Each entry was individually reviewed. Results: 2559 records of food supplements with quality problems were identified in the RASFF, several of which (319 [12,5%]) were marketed to facilitate weight loss. 202 (63,3%) contained unapproved, synthetic drug ingredients. The major adulterant (113 of 319, 35.4%) was DNP (2,4-dinitrophenol), whereas sibutramine was the second most frequent adulterant agent (69 products, 21,6%) between 1988 and 2019. Conclusion: The number of approved medicines for the indication of weight loss is relatively low and their efficacy (and also that of the natural ingredients) is limited. Therefore, a significant number of weight loss supplements is adulterated to satisfy patients’ expectations. Hence, these products may cause serious adverse effects in sensitive patients.